Results of Medium Seventeen Years’ Follow-Up after Laparoscopic Choledochotomy for Ductal Stones - Silvia Quaresima; Andrea Balla; Mario Guerrieri; Giovanni Lezoche; Roberto Campagnacci; Giancarlo D’Ambrosio; Emanuele Lezoche; Alessandro M. Paganini (Gastroenterology Research and Practice)
Introduction. In a previously published article the authors reported the long-term follow-up results in 138 consecutive patients with gallstones and common bile duct (CBD) stones who underwent laparoscopic transverse choledochotomy (TC) with T-tube biliary drainage and laparoscopic cholecystectomy (LC). Aim of this study is to evaluate the results at up to 23 years of follow-up in the same series. Methods. One hundred twenty-one patients are the object of the present study. Patients were evaluated by clinical visit, blood assay, and abdominal ultrasound. Symptomatic patients underwent cholangio-MRI, followed by endoscopic retrograde cholangiopancreatography (ERCP) as required. Results. Out of 121 patients, 61 elderly patients died from unrelated causes. Fourteen patients were lost to follow-up. In the 46 remaining patients, ductal stone recurrence occurred in one case (2,1%) successfully managed by ERCP with endoscopic sphincterotomy. At a mean follow-up of 17.1 years no other patients showed signs of bile stasis and no patient showed any imaging evidence of CBD stricture at the site of choledochotomy. Conclusions. Laparoscopic transverse choledochotomy with routine T-tube biliary drainage during LC has proven to be safe and effective at up to 23 years of follow-up, with no evidence of CBD stricture when the procedure is performed with a correct technique.